APLIKASI METODE FUZZY-SERVQUAL DAN THEORY OF INVENTIVE PROBLEM SOLVING (TRIZ) PADA PENINGKATAN KUALITAS JASA DI KLINIK ABC - Defitri Zakiaturrahmah; Hadi Suprapto; Surya Perdana (Fakultas Teknik Universitas Persada Indonesia YAI, 2022)
ABC Clinic experienced a decrease in the number of consumers from 2019 to 2020 by 76%, thiscaused a loss to ABC Clinic. The purpose of this study was to determine the cause of the decline in thenumber of consumers at ABC Clinic and provide suggestions that could help ABC Clinic in fulfillingconsumer desires. The method used in this research is Fuzzy-Service Quality and Theory of InventiveProblem Solving (TRIZ). The results of this research are the common causes that lead to a decrease in thenumber of visitors at the ABC Clinic are the administrative system and complete blood test equipment arestill manual, sentences delivered by doctors are difficult for patients to understand, do not provide healthfacilities using BPJS Health. The proposal to improve service quality for ABC Clinic is to hold programssuch as family gatherings and external and internal training, to update the technology system andcooperate with the BPJS Kesehatan.